Geographical and intrapopulation variation in the diet of a threatened marine predator, Pontoporia blainvillei (Cetacea) - Henning, Barbara; Sa Carvalho, Benilton de; Pires, Mathias M.; Bassoi, Manuela; Marigo, Juliana; Bertozzi, Carolina; Araujo, Marcio S. [UNESP] (Wiley-Blackwell, 2018)
Understanding diet variation is a major concern when developing conservation guidelines for threatened species, especially for marine predators whose prey availability can be reduced by commercial fisheries. Diet can vary in geographically structured populations due to variation in prey availability and within a location due to the effects of season, sex, age, and individual. However, these sources of variation are seldom considered together in dietary studies. We analyzed diet variation at the geographical and intrapopulation levels in the franciscana dolphin (Pontoporia blainvillei) by analyzing samples of stomach contents from individuals incidentally caught by artisanal fisheries. We investigated the geographical (Northern, Central, and Southern regions of the SAo Paulo State coast, Brazil) and intrapopulation effects of season, sex, and age. We used the leave-one-out cross-validation method to test for significance of the proportional similarity index, which measures the overlap between diet compositions. We found that diet varied across different levels, from the geographical to the individual level, including the effects of season, sex, and age. Diet variation as a function of age suggests an ontogenetic diet shift. Our findings indicate that ecological processes within local stocks should inform management at the local geographic scale. Evidence for ecological differences between franciscana stocks is of great significance for the conservation of this threatened species.
Keywords: conservation; franciscana dolphin; Index of Relative Importance; interindividual variation; ontogenetic diet shift; proportional similarity index; stomach contents